Optical Force Measurements Illuminate Dynamics of Escherichia coli in Viscous Media - Armstrong, Declan J.; Nieminen, Timo A.; Favre-Bulle, Itia; Stilgoe, Alexander B.; Lenton, Isaac C. D.; Schembri, Mark A.; Rubinsztein-Dunlop, Halina (Frontiers in Physics, 2020)
Escherichia coli and many other bacteria swim through media with the use of flagella, which are deformable helical propellers. When the viscosity of media is increased, a peculiar phenomenon can be observed in which the organism's motility appears to improve. This improvement in the cell's swimming speed has previously been explained by modified versions of resistive force theory (RFT) which accounts for the interaction between flagella and molecules associated with the viscosity increase. Using optical tweezers, we measure the swimming force of individual E. coli in solutions of varying viscosity. By using probe-free force measurements, we are able to quantitatively validate and compare RFT and proposed modifications to the theory. We find that the force produced by the flagellum remains relatively constant even when the viscosity of the medium increases by approximately two orders of magnitude, contrary to predictions of RFT and variants. We conclude that the observed swimming forces can be explained by allowing the flagella geometry to deform as the viscosity of the surrounding medium is increased.